A Lung Sound Classification System based on the Rational Dilation Wavelet Transform - Ulukaya, Sezer; Serbes, Gorkem; Sen, Ipek; Kahya, Yasemin P. (IEEE, 2016)
I n this work, a wavelet based classification system that aims to discriminate crackle, normal and wheeze lung sounds is presented. While the previous works related with this problem use constant low Q-factor wavelets, which have limited frequency resolution and can not cope with oscillatory signals, in the proposed system, the Rational Dilation Wavelet Transform, whose Q-factors can be tuned, is employed. Proposed system yields an accuracy of 95 % for crackle, 97 % for wheeze, 93.50 % for normal and 95.17 % for total sound signal types using energy feature subset and proposed approach is superior to conventional low Q-factor wavelet analysis.
Keywords: FREQUENCY; Engineering